THE ROLE OF NIZAMIYYAH MADRASAS IN EDUCATION - Türker GÖKTÜRK (Fırat University, 2019)
A madrasa can be defined as an educational institution whose needs were met by foundations, which provided education in line with mosques, but where the needs of student groups and mudarrises were met by the mosques, after the Turks had accepted Islam as their religion. Besides a madrasa can also be defined as a place which provided education in line with mosques but where the needs (education, learning, traineeship, practice as well as eating, drinking, accommodation, library etc.) of crowded student groups and mudarrises which could not be fulfilled by mosques were met. Our aim for conducting this study was to introduce Nizamiyyah Madrasas, show what type lessons were provided in their structures, and find out that were the targets of these madrasas. And also we aimed to know closely the educational institutions developed by Seljuks after they had become Moslems and find out the similarities between them and today’s educational institutes, attempt to discover educational implementations of Nizamiyyah Madrasas which has an important place in the history, but are believed by us to be studied insufficiently, and see the roles of the madrasas. When it is regarded that this study will fill a gap in the literature because there are not sufficient sources about these madrasas in spite of being quite important in the educational history, our study has a specific importance in this condition. In this study, literature scanning model was used due to unavailability of Nizamiyyah Madrasas in today. It is determined with the performed study that Nizamiyyah Madrasas were established because the education given in the mosques and masjids were insufficient, irregular and unplanned, and there was a rise in the amount of the people who demanded education in the society, and also it played a role in the spreading of Islam and adoption of the state policies by the people. In line with such obtained results, a number of suggestions were made.